USING DIRECT RITZ METHOD FOR SOLVING ELECTROCHEMICAL MACHINING MOVING BOUNDARY PROBLEM - S, Fadhel; H, Sinan (Al-Nahrain Journal of Science, 2010)
In this paper, the objective is to derive the variational formulation of the electrochemicalmachining problem (ECM for short) and to evaluate the numerical solution using the direction Ritzmethod. This problem is of degenerate problem which has so many difficulties to be solved usingother approach.